Study of prevalence of endometrial cancer in patients with adenomyosis uteri - Essmat, Ahmad Abdel Azim (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The aim of the study was to evaluate the prevalence of adenomyosis in endometrial cancer patients and to determine the frequency of adenomyosis and endometrial cancer at hysterectomy specimens. Methods: This study was carried out retrospectively on pathologic specimens of hysterectomies. A total of 98 women in the period May 2020 to January 2021enrolled to the study. All pathologies seen in hysterectomy specimens were noted. The frequency of adenomyosis and the accompanying pathologies were determined. These women were categorized into two groups according to the cause of hysterectomy. The incidence of adenomyosis was analyzed together with the endometrial cancer. Results: The incidence of adenomyosis was 22% at hysterectomy specimens. There was no statistically significant difference between the mean age of the two groups (p=0.002*). There were 22 cases with adenomyosis and the only pathologic finding was adenomyosis, in 22.7% of cases. The most common accompanying pathologies with adenomyosis were uterine myomas in 95% and on significant association was found in cases of endometrial carcinoma. Conclusions: There is no evidence that adenomyosis increases the risk of endometrial cancer as there is no statistically significant difference found between the group with and the group without adenomyosis in terms of coexistence with endometrial carcinoma.